NTERNET SEHAT BAGI SANTRI (Studi Pendampingan Internet bagi Panti Asuhan Di Kabupaten Ponorogo) - Iman, Nurul; ., Katni; Kurniawan, Edy (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
The times in the last decadee has risen a lot of creativity and innovation in life, such asinternet in the information and communication technology. This breakthrough promises an easein communication, access and transfer, and even business transaction. However, the ease of internet facility can not be enjoyed by all people, including orphans, orphanage residents, and thepoor due to their limitedness. Presenting devotion and assistance in accessing the internet for theorphanage students is the form of alleviation from their limitedness, in addition to selfempowerment from any failed.